Predictive torque control of three-level sparse neutral point clamped inverter fed IPMSM drives using simplified deadbeat principle - Zhang, Xinan (2020)
This paper proposes a predictive torque control for interior permanent magnet synchronous machine (IPMSM) driven by three-level sparse neutral point clamped inverter. It contributes to greatly diminish the torque and flux ripples by using predictions and three voltage levels. To precisely synthesize the voltage vectors, deadbeat principle is employed. Different from existing works, the proposed control method is implemented in stationary reference frame, eliminating coordinate transformations. Furthermore, one cycle delay is compensated through predictions. In addition, to further reduce the torque and flux ripples, three-level sparse neutral point clamped inverter (3L-SNPCI) is employed. In comparison with other types of three-level inverters, it utilizes fewer power semiconductors and has alleviated neutral point voltage fluctuation problem. Space vector modulation is employed to generate the switching signals for the 3L-SNPCI. The validity of the proposed approach is verified by experimental results.